Modern therapies for pelvic floor dysfunction in women due to surgical menopause - Tatiana Y. Pestrikova; Anastasia V. Kotelnikova; Elena G. Veselkova; Elena A. Yurasova; Igor V. Yurasov; Natalia V. Strelnikova (Гинекология)
Aim. To compare the effectiveness of the kGoal vaginal trainer combined with the intimate non-hormonal phytocomplex with hyaluronic acid, Estrogial, for the non-surgical treatment of the early stages of pelvic prolapse in women with surgical menopause.